The role of salience in protfolio formation - da Silva Rosa, R.; Durand, Robert (Elsevier, 2008)
We analyze the likelihood of a stock being included in an investor's portfolio, utilizing a dataset whichholds the information opportunity set constant for each of the over 1000 student investors in our sample.Investors rely on the availability heuristic: salience (the number of stories in the national press about a stock in the month before the portfolios are formed) captures over 50% of the variation in our dependent variable.